Introduction of an applicant Job-Related Task Assessment (JTA) and the effects on the health and fitness of police recruits. - Lockie, Robert G.; Orr, Robin M.; Kennedy, Kelly; Dawes, J. Jay (Work, 2024)
BACKGROUND: In 2020, a police department in the south-eastern USA introduced a Job-Related Task Assessment (JTA). The JTA included running, climbing, crawling, balance, direction changes, stair climbing, dragging, pushing, and simulated controlling of a struggling subject and needed to be completed by applicants in 6 : 57 min:s. It is not known whether introducing the JTA in the hiring process affected the health and fitness of hired recruits. OBJECTIVE: To compare the health and fitness of recruits hired prior to, and following, the JTA introduction. METHODS: Analysis was conducted on recruit data split into academy training year: 2016 (n = 91), 2017 (n = 129), 2018 (n = 167), 2019 (n = 242), and 2020 (n = 37). The 2020 group was hired after the JTA introduction and included one academy class. The following were recorded for all recruits: age, height, body mass, and body mass index; systolic and diastolic blood pressure (BP); sit-and-reach; grip strength; push-ups; sit-ups; 2.4-km run; and a physical ability test (PAT). A univariate ANOVA, with sex and age as covariates and Bonferroni post hoc, determined between-year differences. RESULTS: The recruits from 2020 were significantly lighter than 2018 recruits (p < 0.031), had higher systolic and diastolic BP than recruits from 2016–2018 (p≤0.006), completed the 2.4-km run faster than recruits from all years (p < 0.001), and completed the PAT faster than the 2016 and 2019 (p = 0.006–0.007) recruits. CONCLUSION: The JTA introduction led to the selection of recruits with lower body mass, and better aerobic (2.4-km run) and job-specific fitness (PAT). However, 2020 recruits also had higher BP which should be monitored.